Planetary Aeolian Landforms: An Introduction to the Fifth Planetary Dunes Workshop Special Issue. Issue 4 (18th April 2022) - Silvestro, S.; Titus, T. N.
Abstract: Aeolian landforms are widespread in our solar system. Understanding the exact nature and processes of formation of these features are challenging tasks necessitating a strong collaboration between scientists with different skills and scientific backgrounds. This paper describes the special issue for the 5th International Planetary Dunes Workshop, which includes 15 research papers and three commentaries. Among the 18 papers included in this collection, 16 cover Martian aeolian science and two Titan aeolian science. The papers presented focus on bedform morphology and dynamics via remote sensing data, modeling, analogs studies and laboratory experiments. Here we put the main results of the papers in their appropriate scientific context and discuss potential future lines of research. Plain Language Summary: Wind‐sculpted (aeolian) landforms are found on many bodies of our solar system. Their study is fundamental to understanding the geology and climate of these bodies and to safely plan extraterrestrial missions. Here we introduce a collection of papers describing aeolian features on Mars and Titan. Collectively, the papers presented in this special issue show the importance of an interdisciplinary approach in comprehending what we are seeing on other planets. The study of wind landforms in extraterrestrial planets is sparking a new interest on terrestrial aeolian geomorphology highlighting the significance of planetary studies in advancing the understanding of our Earth. Key Points: Results from the 5th International Planetary Dunes Workshop are presented Study of aeolian landforms can shed light on climatic changes and are key for landing site characterization Combined use of imaging and high‐resolution flow modeling can provide new insights into the mechanism and processes that form bedforms